Peran Artificial Intelligence dalam Mitigasi Risiko Transaksi Mobile Banking: Tinjauan Governansi dan Etika Data - Wiriani, Erni; Jauharil Maknuni; Puspita, Esti Alemia; Masitah, Masitah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The advancement of Artificial Intelligence (AI) technology has brought significant transformation in the digital banking sector, particularly in mobile banking services. One of the main challenges in this development is the increasing risk of suspicious transactions, including fraud and data misuse. This study aims to analyze the role of AI in mitigating the risks of suspicious transactions while reviewing the accompanying aspects of data governance and ethics. Using a qualitative approach through literature review and a case study at Bank Syariah Indonesia, Aceh Timur branch, which has implemented an AI-based fraud detection system, research data were obtained from the analysis of internal bank documents, in-depth interviews with IT staff and compliance managers, as well as observations of mobile banking operational processes. The findings indicate that AI is capable of enhancing both speed and accuracy in detecting unusual transaction patterns in real time. However, the effectiveness of AI implementation highly depends on sound technology governance, strict data protection policies, and the system’s alignment with ethical principles and transparency. In addition, the success of risk mitigation is also determined by the ability of financial institutions to maintain algorithm accountability and ensure the absence of bias in automated decision-making. This study emphasizes the importance of synergy between technological innovation and strong governance principles to create a safe, trustworthy, and equitable digital financial system. Recommendations are provided to strengthen internal banking policies related to algorithm auditing, customer data protection, and digital ethics training for AI system developers.